Managing public relations business principles and tools for strategic communication - Smudde, Peter M. (Routledge, 2023)
Managing Public Relations, 2e introduces students to the key concepts and practices involved in the day-to-day running of a PR operation, whether it is a company department, an independent agency, or any organized group focused on PR. The book's unique approach places the PR function within the broader context of an organization, equipping students with the essential business knowledge, perspective, and skills needed when starting out in their careers.